SOCIAL AND EMOTIONAL CHARACTERISTICS OF ADOLESCENT WHO UNDERWENT SOCIAL DISTANCING POLICIES DURING THE COVID-19 PANDEMIC: EMOTIONAL CHARACTERISTICS OF ADOLESCENT WHO UNDERWENT SOCIAL DISTANCING POLICIES DURING THE COVID-19 PANDEMIC - Nur Khotimah Elfiyani; Hadi Pratomo; Safitri Widayanti Putri; Rizki Dhahifa Wahyuni; Ghifari Andini Mukti (Quality : Jurnal Kesehatan, 2021)
COVID-19 has been declared an international public health emergency by WHO. The Indonesian government has issued a policy as a strategy for controlling COVID-19 and encourages the public to carry out social distancing. Social distancing during the COVID-19 pandemic will affect the mental health of adolescents, where there is an increase in negative effects and a decrease in positive influence on adolescent emotional changes. This research is a qualitative study that aims to determine the social emotional picture of adolescents who carry out social distancing during the COVID-19 pandemic, seen from the aspects of behavior, individuals and the environment based on the SCT Bandura theory. The design used is the Rapid Assessment Procedure (RAP) and data collection was carried out by in-depth interviews through the zoom application (video teleconference). The informants were selected by purposive sampling as many as 9 informants consisting of 6 adolescent informants aged 15-24 years and 3 accompanying informants. Data were analyzed using matrices and thematic analysis. The results showed that adolescents felt various changes in relationships with family and peers during social distancing. Social and emotional changes experienced by adolescents such as stress, symptoms of anxiety, symptoms of depression and loneliness.